2021
DOI: 10.1108/mf-12-2020-0601
|View full text |Cite
|
Sign up to set email alerts
|

Calendar anomalies in the stock markets: conventional vs Islamic stock indices

Abstract: PurposeIn this study, the authors evaluate seven calendar anomalies’–the day of the week, weekend, the month of the year, January, the turn of the month (TOM), Ramadan and Eid festivals–effects in both the conventional and Islamic stock indices of Bangladesh. Also, the authors examine whether these anomalies differ between the two indices.Design/methodology/approachThe authors select the Dhaka Stock Exchange (DSE) Broad Index (DSEX) and the DSEX Shariah Index (DSES) of the DSE as representatives of the convent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…Crisis has drastic effect on portfolio returns. Therefore, it is essential to understand the co-movements between crisis and volatility spillovers for optimal risk management (Hasan et al , 2021). This and some other studies, Hassan et al (2022) recommend that policymakers need to take corrective steps to increase awareness and financial literacy among investors to select securities that can minimize the effect of such crises on their portfolio return.…”
Section: Discussionmentioning
confidence: 99%
“…Crisis has drastic effect on portfolio returns. Therefore, it is essential to understand the co-movements between crisis and volatility spillovers for optimal risk management (Hasan et al , 2021). This and some other studies, Hassan et al (2022) recommend that policymakers need to take corrective steps to increase awareness and financial literacy among investors to select securities that can minimize the effect of such crises on their portfolio return.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, over the examination period from January 2015 to December 2018, Shariff et al (2021) found a significant month effect in Bursa Malaysia in May, November, and December. Hasan et al (2021) examined the effects of seven calendar anomalies:(1) January;…”
Section: Literature Reviewmentioning
confidence: 99%
“…Under this assumption, the DH is supported. Recently, Hasan et al (2021) conducted a comparison between Islamic and conventional stock indices considering data from Dhaka Stock Exchange for the period 2011 to 2020. The study reveals that except for the Ramadan effect, both types of indices have similar patterns of calendar anomalies.…”
Section: Literature Reviewmentioning
confidence: 99%